Respuesta :

Answer:

(1, 3 )

Step-by-step explanation:

Given the 2 equations

y = x + 2 → (1)

y = 3x → (2)

Substitute y = 3x into (1)

3x = x + 2 ( subtract x from both sides )

2x = 2 ( divide both sides by 2 )

x = 1

Substitute x = 1 into either of the 2 equations for corresponding value of y

Substituting into (1)

y = 1 + 2 = 3

solution is (1, 3 )

Space

Answer:

(1, 3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right  

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Coordinates (x, y)
  • Solving systems of equations using substitution/elimination

Step-by-step explanation:

Step 1: Define Systems

y = x + 2

y = 3x

Step 2: Solve for x

Substitution

  1. Substitute in y:                                                                                                3x = x + 2
  2. [Subtraction Property of Equality] Subtract x on both sides:                      2x = 2
  3. [Division Property of Equality] Divide 2 on both sides:                                x = 1

Step 3: Solve for y

  1. Define original equation:                                                                               y = 3x
  2. Substitute in x:                                                                                                y = 3(1)
  3. Multiply:                                                                                                           y = 3